Molecular and Biochemical Analysis of Chalcone Synthase from Freesia hybrid in Flavonoid Biosynthetic Pathway - Sun, Wei; Meng, Xiangyu; Liang, Lingjie; Jiang, Wangshu; Huang, Yafei; He, Jing; Hu, Haiyan; Almqvist, Jonas; Gao, Xiang; Wang, Li (PLOS ONE, 2015)
Chalcone synthase (CHS) catalyzes the first committed step in the flavonoid biosynthetic pathway. In this study, the cDNA (FhCHS1) encoding CHS from Freesia hybrida was successfully isolated and analyzed. Multiple sequence alignments showed that both the conserved CHS active site residues and CHS signature sequence were found in the deduced amino acid sequence of FhCHS1. Meanwhile, crystallographic analysis revealed that protein structure of FhCHS1 is highly similar to that of alfalfa CHS2, and the biochemical analysis results indicated that it has an enzymatic role in naringenin biosynthesis. Moreover, quantitative real-time PCR was performed to detect the transcript levels of FhCHS1 in flowers and different tissues, and patterns of FhCHS1 expression in flowers showed significant correlation to the accumulation patterns of anthocyanin during flower development. To further characterize the functionality of FhCHS1, its ectopic expression in Arabidopsis thaliana tt4 mutants and Petunia hybrida was performed. The results showed that overexpression of FhCHS1 in tt4 mutants fully restored the pigmentation phenotype of the seed coats, cotyledons and hypocotyls, while transgenic petunia expressing FhCHS1 showed flower color alteration from white to pink. In summary, these results suggest that FhCHS1 plays an essential role in the biosynthesis of flavonoid in Freesia hybrida and may be used to modify the components of flavonoids in other plants.